Invasive Corridor of Clivus Extension in Pituitary Adenoma: Bony Anatomic Consideration, Surgical Outcome and Technical Nuances - Wu, Xiao; Ding, Han; Yang, Le; Chu, Xuan; Xie, Shenhao; Bao, Youyuan; Wu, Jie; Yang, Youqing; Zhou, Lin; Li, Minde; Li, Shao Yang; Tang, Bin; et al. (Frontiers in Oncology, 2021)
Background It is well known that the clivus is composed of abundant cancellous bone and is often invaded by pituitary adenoma (PA), but the range of these cancellous bone corridors is unknown. In addition, we found that PA with clivus invasion sometimes accompanied by petrous apex invasion, so we speculated that the petrous apex tumor originated from the clivus cancellous bone corridor. The aim of this study was to test this hypothesis by investigating the bony anatomy associated with PA with clival invasion and its clinical significance. Methods Twenty-two cadaveric heads were used in the anatomical study to research the bony architecture of the clivus and petrous apex, including six injected specimens for microsurgical dissection and sixteen cadavers for epoxy sheet plastination. The surgical videos and outcomes of PA with clival invasion in our single center were also retrospectively reviewed. Results The hypoglossal canal and internal acoustic meatus are composed of bone canals surrounded by cortical bone. The cancellous corridor within clivus starts from the sellar or sphenoid sinus floor and extends downward, bypassing the hypoglossal canal and finally reaching the occipital condyle and the medial edge of the jugular foramen. Interestingly, we found that the cancellous bone of the clivus was connected with that of the petrous apex through petroclival fissure extending to the medial margin of the internal acoustic meatus instead of a separating cortical bone between them as it should be. It is satisfactory that the anatomical outcomes of the cancellous corridor and the path of PA with clival invasion observed intraoperatively are completely consistent. In the retrospective cohort of 49 PA patients, the clival component was completely resected in 44 (89.8%), and only 5 patients in the early-stage had partial residual cases in the inferior clivus. Conclusion The petrous apex invasion of PA is caused by the tumor invading the clivus and crossing the petroclival fissure along the cancellous bone corridor. PA invade the clivus along the cancellous bone corridor and can also cross the hypoglossal canal to the occipital condyle. This clival invasion pattern presented here deepens our understanding of the invasive characteristics of PA.